Illustration process in visual communication: a qualitative study on storybook product development - Arifin, Irfan; Hasbi, Hasbi (International Journal of Visual and Performing Arts, 2025)
The illustration process in visual communication design plays a critical role in supporting product development; however, there remains a lack of systematic and empirical studies that examine its practical stages within the design research context, particularly in the field of storybook illustration. This study aims to identify and describe the stages of the illustration process specifically applied in the development of storybook products. A qualitative descriptive case study approach was used, with data collected through literature review, in-depth interviews with four professional illustrators, and document analysis. The data were analyzed using content analysis techniques to extract patterns of practice and define the illustration workflow. The findings reveal an integrated, eleven-stage illustration process that includes narrative exploration, concept development, sketching, refinement, visual enhancement, layout, validation, and final presentation. This process is shown to be iterative, reflective, and context-sensitive, rather than strictly linear. The study contributes a structured conceptual model of the illustration process in design practice, providing theoretical insights and a practical reference for researchers, educators, and practitioners in visual communication design.